The Effectiveness of Self-Study in Improving the Grammar Competence of Students of the Department of Food Science and Agricultural Product Technology: A Classroom-Based Investigation - Marnita, Rina (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study investigates the effectiveness of self-study as a supplementary strategy for improving grammar competence among first-year students in the Department of Food Science and Agricultural Product Technology at a public university in West Sumatra, Indonesia. Conducted within a General English course limited to six class meetings, the study addressed the challenge of grammar instruction in a heterogeneous classroom. A self-study module, comprising curated online resources and structured assignments, was implemented to support grammar learning outside classroom hours. Findings indicate a marked improvement in grammar scores, particularly among students with lower initial proficiency levels. Self-assessment and perception surveys also showed a high level of engagement and acceptance of the self-study approach. These results suggest that structured self-study can be an effective method to complement formal instruction in time-constrained, diverse educational settings. Contribution to Sustainable Development Goals (SDGs):SDG 4: Quality Education